Identification and Validation in a Novel Quantification System of Ferroptosis Patterns for the Prediction of Prognosis and Immunotherapy Response in Left- and Right-Sided Colon Cancer - Zhang, Heng-Chun; Deng, Shen-Hui; Pi, Ya-Nan; Guo, Jun-Nan; Xi, Hua; Shi, Xin; Yang, Xue-Fei; Zhang, Bo-Miao; Xue, Wei-Nan; Cui, Bin-Bin; Liu, Yan-Long (Frontiers in Immunology, 2022)
Background: This study aimed to establish a novel quantification system of ferroptosis patterns, comprehensively analyze the relationship between ferroptosis score (FS) and the immune cell infiltration (ICI) characterization, tumor mutation burden (TMB), prognosis, and therapeutic sensitivity in left-sided and right-sided colon cancers (LCCs and RCCs, respectively). Methods: We comprehensively evaluated the ferroptosis patterns in 444 LCCs and RCCs based on 59 ferroptosis-related genes (FRGs). The ferroptosis score (FS) was constructed to quantify ferroptosis patterns by using principal component analysis algorithms. Next, the prognostic value and therapeutic sensitivities were evaluated using multiple-method. Finally, we performed WGCNA to identify the key FRGs. The IMvigor210 cohort, TCGA COAD proteomics cohort and Immunophenoscores were used to verified the predictive abilities of FS and the key FRGs. Results: Two ferroptosis clusters were determined. Ferroptosis cluster B demonstrated a high degree of congenital ICI and stromal related signals enrichment with poor prognosis. The Prognosis, response of targeted inhibitors and immunotherapy were significantly different between high and low FS groups (HSG and LSG, respectively). HSG was characterized by high TMB and microsatellite instability-high subtype with poor prognosis. Meanwhile, LSG was more likely to benefit from immunotherapy. ALOX5 was identified as key FRG based on FS. Patients with high protein levels of ALOX5 had poorer prognoses. Conclusion: This work revealed that the evaluation of ferroptosis subtypes will contribute to gaining our insights into the heterogeneity in LCCs and RCCs. The quantification for ferroptosis patterns played a nonnegligible role in predicting ICI characterization, prognosis and individualized immunotherapy strategies.